Long Non-coding RNAs Are Differentially Expressed After Different Exercise Training Programs - Bonilauri, Bernardo; Dallagiovanna, Bruno (Frontiers in Physiology, 2020)
Background Molecular regulation related to the health benefits of different exercise modes remains unclear. Long non-coding RNAs (lncRNAs) have emerged as an RNA class with regulatory functions in health and diseases. Here, we analyzed the expression of lncRNAs after different exercise training programs and their possible modes of action related to physical exercise adaptations. Methods Public high-throughput RNA-seq data (skeletal muscle biopsies) were downloaded, and bioinformatics analysis was performed. We primarily analyzed data reports of 12 weeks of resistance training (RT), high-intensity interval training (HIIT), and combined (CT) exercise training. In addition, we analyzed data from 8 weeks of endurance training (ET). Differential expression analysis of lncRNAs was performed, and an adjusted P-value < 0.1 and log2 (fold change) ≥0.5 or ≤−0.5 were set as the cutoff values to identify differentially expressed lncRNAs (DELs). Results We identified 204 DELs after 12 weeks of HIIT, 43 DELs after RT, and 15 DELs after CT. Moreover, 52 lncRNAs were differentially expressed after 8 weeks of ET. The lncRNA expression pattern after physical exercise was very specific, with distinct expression profiles for the different training programs, where few lncRNAs were common among the exercise types. LncRNAs may regulate molecular responses to exercise, such as collagen fibril organization, extracellular matrix organization, myoblast and plasma membrane fusion, skeletal muscle contraction, synaptic transmission, PI3K and TORC regulation, autophagy, and angiogenesis. Conclusion For the first time, we show that lncRNAs are differentially expressed in skeletal muscle after different physical exercise programs, and these lncRNAs may act in various biological processes related to physical activity adaptations.